Improving production performance of dairy animals in the villages by strategic supplementation -on farm trial - SAMPATH, K T; CHANDRASEKHARAIAH, M; PRAVEEN, U S (The Indian Journal of Animal Sciences, 2011)
Two on-farm lactation trials of 8 months duration each were conducted in villages, Anagalpura and Menesi, respectively of Doddaballapura taluk of Bangalore district in Karnataka state to study the effect of strategic supplementation on the basal diet in lactating crossbred cows. On-farm trials in each village were divided into 2 phases based on the availability of basal roughage (phase 1: local green grass + fingermillet straw; phase 2: local green grass alone). Phase 1 lasted for 5 months followed by phase 2 continuously for 3 months duration. Crossbred cows (22) yielding 8 to 10 Htres of milkJ day, were divided into 2 groups (control and experimental) of 11 each in Anagalpura village and 16 crossbred cows (8 to 10 litres milk/day) were divided into 8 each in Menesi village based on lactation number, milk yield and days after calving. In both the villages, the cows in control group were fed with supplements of groundnut cake and wheat bran as practised by the fanners in phase 1 and 2. Animals in experimental group (in both the phases) were fed supplements, viz. groundnut cake, wheat bran and maize grain by replacing part of wheat bran in this group. The animals in both the groups were fed the basal roughage as mentioned in phase 2 and 1. The average milk yield/day in experimental group was significantly higher than those in control group in Anagalpura and Menesi villages. Milk fat, total solids and SNF were significantly higher in experimental group than that in control group irrespective of the phases in both the villages. The farmers income increased by Rs 15.73 and Rs 11.59/cow/day respectively, in phase I and 2 in Anagalpura and Rs 8.95 and Rs. 16.98/cow/day respectively, in phase 1 and 2 in Menesi villages by improved method of feeding. The study indicated that strategic supplementation of limiting nutrients i.e. energy through maize grain to the local available basal diets increased milk yield and had a positive effect on milk composition. Hence it was delnonstrated that with minitnurn alternation in the existing feeding practices by scientific intervention, the farmers income can be increased through enhanced milk production. Â